PERBANDINGAN PERFORMA MOTOR BAKAR DENGAN MENGGUNAKAN GAS LPG - Junaidi, Junaidi; Ritonga, Din Aswan Amran (JiTEKH, 2020)
Technological developments with the number and growth of motorized vehicles and the consumption of fuel oil in Indonesia have caused problems for the environment and fuel supply. This problem is even more complicated because the subsidy for its procurement is already very burdensome to the State Revenue and Expenditure Budget. Therefore, comprehensive efforts must continue to be made to find the best solution. This paper discusses the results of research aimed at reducing emissions and reducing motorcycle fuel consumption, by converting the use of gasoline to LPG which is commonly used for cooking. Tests were carried out in the laboratory using a chassis dynamometer to compare torque, power, fuel consumption levels and operating costs, on a carburetor motorcycle engine using gasoline and LPG, either without changing the ignition conditions or by changing the ignition conditions. From this study it was found that LPG fuel has good performance and can be used directly without changing the ignition conditions. However, the performance will be better if the ignition conditions are adjusted. The best level of LPG consumption is 86 km/kg or Rp.58/km, while gasoline is 66 km/l or Rp.98/km.